KONTRIBUSI KEMAMPUAN MANAJEMEN KELAS, IKLIM SEKOLAH DAN ETOS KERJA TERHADAP HASIL BELAJAR INFORMATIKA - Fahmi, Merdila Nuril; Basra, Sri Meiweni; Trinanda, Jessica; Ilham, Fadli (Information Technology Education Department, 2024)
This study aims to determine the relationship between classroom management skills, school climate and work ethic partially and together with the informatics learning outcomes of class X students at SMKN 1 Painan. The research method used is quantitative correlational. The population in the study were all class X students at SMKN 1 Painan totaling 402 people. The research sample was 80 people drawn by proportional random sampling. The test results at a significance level of α 0.05 (95% confidence level) obtained a rx1y value of 0.969 with rtable 0.220 because rcount> rtable then the first hypothesis is accepted. Then the rx2y value is 0.969 with rtable 0.220, because rcount> rtable then the second hypothesis is accepted. Then the rx3y value is 0.970 with rtable 0.220, because rcount> rtable then the third hypothesis is accepted. Furthermore, the value of rx1x2x3y is 0.976 with rtable 0.220, because rcount> rtable then the fourth hypothesis is accepted. And supported by the value of Fcount = 518.764 and Ftable = 1.454 so that Fcount> Ftable (518.764> 1.454) is obtained. The implications of the research results are improving classroom management skills, improving school climate and improving teacher work ethic.